PERENCANAAN ULANG ANGGARAN BIAYA DAN WAKTU PELAKSANAAN GEDUNG PERKULIAHAN DENGAN MENGGUNAKAN METODE BIM - Rizky Ilham Mardhani; Anik Ratnaningsih; Syamsul Arifin (Rekayasa Sipil, 2022)
The speed of completing all stages of the project will cause major complications in the construction management system. The BIM method can integrate all projects that can save costs and time so that it is effective and makes it easier to coordinate in order to streamline the project. The purpose of this study is the planning of a 7-story economic and business building at the University of Jember using BIM application and steps to mmodel the building using a cost and time budget. In this research, the stages in structure modeling using BIM aids, the results, the results of reinforcement modeling and the required budget plan are Rp. 9,400.450.878.04 the time required is 189 days or 6 months 9 days.